Modernizing Operations: Leveraging GIS in Drilling, Blasting and Quarry Applications - Elijah Williams; Dr. Anurag Agrawal; Steve Franklin; Clint Zimmerman (International Society of Explosives Engineers, 2025)
In a time when data has become a highly valued commodity within many mining and quarry operations, managing large amounts of current and historical information can be difficult. If not managed properly, trying to leverage the data to make informed operational decisions promotes another challenge. Geographic Information System (GIS) is an environment that uses computers and software to create, manage, analyze, and map all types of data. Currently, the mining industry is faced with a challenge to produce the demanded critical metals and minerals that drive our economies. GIS is leveraged in many large mining industries today to help drive decisions, save cost and plan for future operations. Specifically in the Drilling, Blasting and Quarrying industries, data is being captured at many different levels, whether it is a subsurface geological, blast performance, quarry surveys, loading and hauling, or crushing performance. Pen and paper logs and reports compiled lack the dimension that GIS can bring for extracting value from real-time or historical data. GIS connects data to maps, integrating location data with all types of descriptive information. Paired with Artificial Intelligence, additional analytical layers can be built on platforms to extract data and automate workflows. Having the ability to encompass several forms of collected data to drive operational decisions can bring huge savings to the bottom-line. This paper will dive into the areas where GIS data can drive value into operations by assisting in the management and analysis of the types of data being captured, specifically with Drill and Blast. Whether it is tracking haul road conditions, monitoring locations of equipment, environmental conditions, quantifying blast performance or developing a quarry plan based on geological models. GIS can collectively encompass all of this data to bring tremendous value to the operations, improving safety, efficiency and production.